Changes in Sexuality and Quality of Couple Relationship During the COVID-19 Lockdown - Panzeri, Marta; Ferrucci, Roberta; Cozza, Angela; Fontanesi, Lilybeth (Frontiers in Psychology, 2020)
COVID-19 pandemic is heavily influencing people's general wellbeing worldwide. Since the outbreak of the COVID-19 virus, many studies are exploring the general psychological wellbeing of the population, while only a few studies are addressing how COVID-19 pandemic and the lockdown are affecting sexuality. Sexual health, an important aspect of general wellbeing, has relevant consequences on people's daily life. While it is well known that distress can affect sexuality and it is possible to speculate that psychological outbreak outcomes are affecting population sexual life, recent literature doesn’t explore couples’ sexuality and the quality of relationship during the lockdown. The present preliminary research aims to understand if and how sexuality has changed in the Italian population since the spread of the COVID 19, and what are the variables influencing the quality of couple relationship during the COVID 19 lockdown. A questionnaire reserved for cohabiting couples was designed and distributed online from 11th April 2020 (5th week after the start of the lockdown) to 5th May 2020 (8th week after the start of the lockdown). In total, 124 respondents completed the online survey, and of these about 73% were female. Despite the psychological consequences of the pandemic, most couples did not perceive any differences in their sexuality when asked directly. Some female participants reported a decrease in pleasure, satisfaction, desire, and arousal. Worry, lack of privacy, and stress appear to be the main reasons behind the changes in sexuality in women. Even if participants seem to show high levels of resilience, the negative aspects of lockdown can affect the quality of sexual life. This study needs to be completed with qualitative data from online focus groups investigating how sexual life has changed and the main needs of couples. Nevertheless, our results will serve to better address population needs and experiences, and provide ad hoc interventions for this unprecedented time of crisis.